ISLAMIC RELIGIOUS EDUCATION TEACHER STRATEGIES IN INTERNALIZING CHARACTER VALUES IN MADRASAH IBTIDAIYAH STUDENTS - Karwadi; Deni indrawan (Jurnal Cakrawala Pendas, 2023)
The background of the research problem is that there are still students who still do not have characters such as courtesy to teachers. The purpose of this study is to analyze the PAI teacher's strategy in the process of internalizing character values to students.  The type of research used is qualitative with a descriptive approach. Research data were collected through interviews and observation techniques. Interviews were conducted with the head of madrasah, deputy head of curriculum, teachers, and students. Meanwhile, observations were made of student activities with teachers, both in class and outside the classroom.  Data validity was tested using source and method triangulation. Data analysis techniques were carried out with the stages of data reduction, data presentation, and conclusion drawing. The results showed that PAI teachers applied strategies of student self-empowerment (self-efficacy), habituation (conditioning), and the realization of a caring environment (caring community). While the key to success lies in self-exemplary, personal commitment of teachers, and full service. The results of this study provide benefits for the world of education regarding how strategies in shaping children's character. Latar belakang masalah penelitian ialah masih terdapat siswa yang masih tidak mempunyai karakter seperti sopan santun pada guru. Tujuan  penelitian ini adalah menganalisis strategi guru PAI dalam proses internalisasi nilai karakter kepada siswa.  Jenis penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Data penelitian dikumpulan melalui teknik wawancara dan observasi. Wawancara dilakukan kepada kepala madrasah, wakil kepala bidang kurilulum, guru, dan siswa. Sementara itu, observasi dilakukan terhadap kegiatan siswa bersama guru, baik di kelas maupun di luar kelas.  Keabsahan data diuji menggunakan triangulasi sumber dan metode. Teknik analisis data dilakukan dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan guru PAI menerapkan strategi pemberdayaan diri siswa (self-efficacy), pembiasaan (conditioning), dan perwujudanlingkungan yang peduli (caring community). Sedangkan kunci keberhasilannya terletak pada keteladanan diri, komitmen pribadi guru, dan layana penuh. Hasil penelitian ini memberikan manfaat bagi dunia pendidikan mengenai bagaimana strategi dalam membentuk karakter anak.